Elementos de urbanismo azul: lagos naturales y artificiales (2016)
The article approaches a key component of blue urbanism: urban lakes, whether natural or artificial. It studying the close relationship of these bodies of water with the origin of cities and its deterioration to be transformed over time in landfills of residential and industrial wastewater. It’s analysed: the services and benefits that these blue spaces bring to cities and environmental; the phenomena involving higher threats; and some elements for its restoration or rehabilitation. It is concluded that rehabilitate or restore urban lakes wherever they are degraded is a task of urban planners and designers.